PENGARUH PEMBERIAN SERBUK CENGKEH (Syzygium Aromaticum) PADA RANSUM TERHADAP PERFORMAN AYAM RAS PEDAGING (BROILER) - Kiramang, Khaerani; Jufri, Muhammad (Teknosains, 2013)
This research is aim to know the effect feeding of cloves powder (Syzygium aromaticum ) to the performans of the chickens. This research involved 84 broiler chickens that are divided into 4 (four) treatments by the addition of cloves powder of Syzygium aromaticum 0,5%, 0,75%, 1,0%, and 1,25% to the ration. Each treatment was repeated 3 (three) times. Each treatment contain 7 (seven) chickens. Performans that measured are feed consumption, body weight rate and carcas percentation. Data analysis using variance/anova of the Completely Randomized Design (CRD). These results indicate that the addition of cloves powder (Syzygium aromaticum) has no real effect of the Performans of the chickens (P>0,05).Keywords: Powder of Syzygium aromaticum, performans, feeding, broilers.